Komunitas Lamun di Pulau Barranglompo Makassar: Kondisi dan Karakteristik Habitat - ., Supriadi; Kaswadji, Richardus F; Bengen, Dietrich G; Hutomo, Malikusworo (UNIVERSITAS SRIWIJAYA, 2012)
ABSTRACTIndicationÃ‚Â onÃ‚Â seagrassÃ‚Â declineÃ‚Â Ã‚Â hasÃ‚Â beenÃ‚Â observedÃ‚Â inÃ‚Â manyÃ‚Â placesÃ‚Â includingÃ‚Â BarranglompoÃ‚Â IslandÃ‚Â ofÃ‚Â Makassar.Ã‚Â ConditionÃ‚Â ofÃ‚Â damagedÃ‚Â seagrassÃ‚Â hasÃ‚Â significantÃ‚Â impactsÃ‚Â toÃ‚Â theÃ‚Â rolesÃ‚Â ofÃ‚Â seagrassÃ‚Â asÃ‚Â habitat,Ã‚Â spawningÃ‚Â ground,Ã‚Â andÃ‚Â feedingÃ‚Â groundÃ‚Â forÃ‚Â variousÃ‚Â marineÃ‚Â organismsÃ‚Â andÃ‚Â alsoÃ‚Â roleÃ‚Â ofÃ‚Â seagrassÃ‚Â asÃ‚Â carbonÃ‚Â absorbentÃ‚Â andÃ‚Â stocks.Ã‚Â Ã‚Â InÃ‚Â orderÃ‚Â toÃ‚Â provideÃ‚Â aÃ‚Â referenceÃ‚Â forÃ‚Â appropriateÃ‚Â seagrassÃ‚Â managementÃ‚Â andÃ‚Â conservation,Ã‚Â itÃ‚Â isÃ‚Â requiredÃ‚Â dataÃ‚Â onÃ‚Â seagrassÃ‚Â habitat.Ã‚Â Ã‚Â AÃ‚Â researchÃ‚Â wasÃ‚Â doneÃ‚Â inÃ‚Â BarranglompoÃ‚Â Island,Ã‚Â MakassarÃ‚Â fromÃ‚Â DecemberÃ‚Â 2010Ã‚Â toÃ‚Â NovemberÃ‚Â 2011.Ã‚Â Ã‚Â SeagrassÃ‚Â conditionÃ‚Â wasÃ‚Â observedÃ‚Â basedÃ‚Â onÃ‚Â McKenzieÃ‚Â etÃ‚Â al.Ã‚Â (2001)Ã‚Â andÃ‚Â BalestriÃ‚Â etÃ‚Â al.Ã‚Â (2003).Ã‚Â Ã‚Â ThisÃ‚Â researchÃ‚Â showedÃ‚Â thatÃ‚Â largeÃ‚Â seagrassÃ‚Â coverageÃ‚Â wasÃ‚Â dispersedÃ‚Â inÃ‚Â southern,Ã‚Â westernÃ‚Â andÃ‚Â northernÃ‚Â sidesÃ‚Â ofÃ‚Â theÃ‚Â island.Ã‚Â Meanwhile,Ã‚Â seagrassÃ‚Â spesiesÃ‚Â withÃ‚Â widerÃ‚Â distributionÃ‚Â wereÃ‚Â E.Ã‚Â acoroides,Ã‚Â T.Ã‚Â hemprichiiÃ‚Â andÃ‚Â C.rotundata.KeywordsÃ‚Â :Ã‚Â seagrass,Ã‚Â BarranglompoÃ‚Â Island,Ã‚Â habitatÃ‚Â characteristicsÃ‚Â ABSTRAKIndikasiÃ‚Â adanyaÃ‚Â penurunanÃ‚Â kondisiÃ‚Â lamunÃ‚Â ditemukanÃ‚Â diÃ‚Â beberapaÃ‚Â tempatÃ‚Â termasukÃ‚Â diÃ‚Â PulauÃ‚Â BarranglompoÃ‚Â Makassar.Ã‚Â KondisiÃ‚Â lamunÃ‚Â yangÃ‚Â rusakÃ‚Â berimplikasiÃ‚Â terhadapÃ‚Â perananÃ‚Â lamunÃ‚Â sebagaiÃ‚Â habitat,Ã‚Â tempatÃ‚Â memijahÃ‚Â danÃ‚Â tempatÃ‚Â mencariÃ‚Â makanÃ‚Â berbagaiÃ‚Â organismeÃ‚Â sertaÃ‚Â peranÃ‚Â lamunÃ‚Â sebagaiÃ‚Â penyerapÃ‚Â danÃ‚Â penyimpanÃ‚Â karbon.Ã‚Â Ã‚Â SebagaiÃ‚Â dasarÃ‚Â untukÃ‚Â melakukanÃ‚Â pengelolaanÃ‚Â danÃ‚Â konservasiÃ‚Â lamunÃ‚Â yangÃ‚Â tepatÃ‚Â diperlukanÃ‚Â dataÃ‚Â kondisiÃ‚Â danÃ‚Â habitatÃ‚Â lamun.Ã‚Â Ã‚Â PenelitianÃ‚Â dilakukanÃ‚Â diÃ‚Â PulauÃ‚Â BarranglompoÃ‚Â MakassarÃ‚Â dariÃ‚Â bulanÃ‚Â DesemberÃ‚Â 2010Ã‚Â sampaiÃ‚Â NovemberÃ‚Â 2011.Ã‚Â Ã‚Â KondisiÃ‚Â lamunÃ‚Â diamatiÃ‚Â berdasarkanÃ‚Â McKenzieÃ‚Â etÃ‚Â al.Ã‚Â (2001)Ã‚Â danÃ‚Â BalestriÃ‚Â etÃ‚Â al.Ã‚Â (2003).Ã‚Â Ã‚Â PenelitianÃ‚Â menunjukkanÃ‚Â bahwaÃ‚Â distribusiÃ‚Â lamunÃ‚Â yangÃ‚Â luasÃ‚Â ditemukanÃ‚Â padaÃ‚Â sisiÃ‚Â selatan,Ã‚Â baratÃ‚Â danÃ‚Â utaraÃ‚Â pulau.Ã‚Â Ã‚Â JenisÃ‚Â lamunÃ‚Â yangÃ‚Â mempunyaiÃ‚Â sebaranÃ‚Â yangÃ‚Â luasÃ‚Â adalahÃ‚Â E.Ã‚Â acoroides,Ã‚Â T.Ã‚Â hemprichiiÃ‚Â danÃ‚Â C.Ã‚Â rotundata.KataÃ‚Â kunciÃ‚Â :Ã‚Â lamun,Ã‚Â pulauÃ‚Â Barranglompo,Ã‚Â karakteristikÃ‚Â habitat